Classificação climática da bacia hidrográfica do rio doce - Allocca, Rodson de Andrade (2023)
Knowledge of environmental conditions is an element of great importance for the establishment and development of societies. In this sense, among the approaches related to natural dynamics, the understanding of climatic characteristics is a way to better direct and establish the relationship between society and nature. Proposals for climate classification prepared for the Brazilian territory, due to their generalism, often do not provide detailed information in relation to smaller geographic areas. For this reason and the direct influence of climate on health, well-being and even on the development of various economic activities in human societies, a systematization of classification of the dynamics of climate elements is necessary that can provide greater subsidies for planning and the management of anthropic actions on a more detailed scale. The objective of this work is to elaborate the climatic classification of the Rio Doce Hydrographic Basin and the choice of the study area is justified by its national importance in the context of the use of water resources to meet the population demands in its different uses, covering several cities both in the state of Minas Gerais, as in the state of Espírito Santo. This classification is based on the Novais Climate Classification method (2019), adapting the use of the Dinamica EGO environmental modeling software as an intermediate tool in the processing and spatialization of data. For the delimitation of climatic units, reanalysis data from the Climatologies at high resolution for the earth's land surface areas (CHELSA) algorithm, prepared by Karger et al. (2017), were used. The use of reanalysis data is a technical resource that allows obtaining information on the climatic characteristics of areas without official stations, optimizing the provision of data on the national territory. The adopted method is still under construction, as some areas of the Brazilian territory have not yet been classified at all hierarchical levels. As a research hypothesis, we have the perspective that it is possible to refine the climate classification in the study area, since the Novais (2019) classification system is structured in hierarchies, allowing, following defined criteria, a variation in scalar levels, allowing smaller areas can be classified in greater detail. In this system, the classification can be divided into Climatic Zones, Zonal Climates, Climatic Domains, Climatic Subdomains, Climatic Types, Climatic Subtypes, Mesoclimates and Topoclimates. The establishment of climate units according to Novais (2019) has as criteria the average temperature of the coldest month (ATCM), the number of dry months, the influence and performance of atmospheric systems on the rainfall regime and the passage of cold fronts allowing the occurrence of frosts. With the application of the method, the choice of which is related to its great approach potential, it was possible to delimit 76 climatic subtypes at the basin level, in addition to representing an advance in climate analysis at lower geographic scales, as it established 6 Mesoclimates and 5 Topoclimates in the municipality of Ponte Nova, MG. The information generated through the classification, as it contemplates different levels of scalar approach, can, therefore, be used in decision-making regarding the planning and environmental management of the area, in addition to being a contribution to the construction and application of the method for the entire Brazil.